Based on multi-layer gradient threshold CFRP plates defects detection system - Feng, Yuxiang; Guo, Wenjing; Ju, Xiang (Oficyna Wydawnicza Politechniki Wrocławskiej, 2025)
Carbon fiber reinforced plastic (CFRP) is widely used in fields such as aircraft and construction due to its advantages of light weight, high hardness, wear and corrosion resistance. To quantitatively detect internal defects in CFRP panels, a THz reflective defect detection system was built. A defect analysis algorithm based on multi-layer gradient threshold is proposed. Based on the manufacturing process of CFRP, a THz wave echo function model for multi-layer CFRP structures was derived. A CFRP plate containing debonding defects and crack defects was trial produced, to obtain its THz time-domain spectrum. The experiment completed the reconstruction of THz two-dimensional images of CFRP plates. The test results show that three different depths of test data can be detected, and the calculated diameters of the debonding defect areas are 9.12, 9.86, and 9.93 mm, respectively, with a relative error mean of 3.63%. Crack defects can also be effectively identified, but the quality of their test images will decrease with increasing pre-embedded depth. The linearity between defect depth and testing frequency is 0.98, which verifies the possibility of quantitative calculation. The test results of power spectral density and defect depth show that it has good uniformity.
Optica Applicata, Vol. 55, 2025, nr 2, s. 257-267
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; defects detection; carbon fiber reinforced plastic; multi-layer gradient threshold algorithm; THz spectrum